SYSTEMATIZATION OF MICROBIAL SPECIES COMPOSITION PHASE CONSISTING OF JET FUEL - Бойченко, С. В.; Шкільнюк, І. О.; Новак, А .О. (Science-based technologies, 2014)
In the article the problem of microbial contamination of aviation fuels. The main types of microorganisms that cause biodeterioration of aviation fuels are subject to their development and types of hydrocarbons consumed them. Influence of microbial lesions on physical, chemical and performance properties, in particular standard aviation fuel, the fuel system of the aircraft and flight safety. Analyzed the mechanism of degradation of hydrocarbon jet fuel and the effects of this process, carried systematization of microorganisms using taxonomic categories. The classification of microbial destructors for activity development in the aviation fuel (active destructors; potential destructors, partially adapted to the environment and occasional species). Identified key biodestruction aviation fuels – Cladosporium resinae «kerosene fungus» (Hormoconis resinae).